2015
DOI: 10.1016/j.celrep.2015.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Interplay between Astrocytes and Neurons Regulates Endocannabinoid Action

Abstract: Summary The endocannabinoid 2-arachidonoylglycerol (2-AG) is a retrograde lipid messenger that modulates synaptic function, neurophysiology, and behavior. 2-AG signaling is terminated by enzymatic hydrolysis—a reaction that is principally performed by monoacylglycerol lipase (MAGL). MAGL is broadly expressed throughout the nervous system, and the contributions of different brain cell types to regulating 2-AG activity have remained unclear. Here, we genetically dissect the cellular anatomy of MAGL-mediated 2-AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 53 publications
11
104
1
Order By: Relevance
“…5E). These results, when combined with previous findings (36,39,41), indicate that blockade of the principal 2-AG biosynthetic and degradation enzymes in the brain, DAGLα and MAGL, respectively, produces overlapping (reductions in brain prostaglandins and cytokines), but distinct (suppression versus enhancement of anapyrexia) effects on LPS-induced neuroinflammation.…”
Section: Dagl Inhibitors Attenuate Neuroinflammatory Responses In Vivosupporting
confidence: 60%
See 2 more Smart Citations
“…5E). These results, when combined with previous findings (36,39,41), indicate that blockade of the principal 2-AG biosynthetic and degradation enzymes in the brain, DAGLα and MAGL, respectively, produces overlapping (reductions in brain prostaglandins and cytokines), but distinct (suppression versus enhancement of anapyrexia) effects on LPS-induced neuroinflammation.…”
Section: Dagl Inhibitors Attenuate Neuroinflammatory Responses In Vivosupporting
confidence: 60%
“…Monoacylglycerol lipase (MAGL or MGLL)-mediated hydrolysis of 2-AG provides a major source of AA substrate for prostaglandin synthesis in the nervous system under basal and neuroinflammatory states (36)(37)(38)(39). Having discovered that acute, pharmacological inhibition of DAGLs coordinately lowers 2-AG and prostaglandin content of the brain (Fig.…”
Section: Dagl Inhibitors Attenuate Neuroinflammatory Responses In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Biosynthetic enzymes as well as FAAH and MAGL are expressed in astrocytes (827,861). A recent study genetically dissected the cellular anatomy of MAGLmediated 2-AG metabolism in the brain and showed that neurons and astrocytes coordinately regulate 2-AG levels and CB1-mediated synaptic plasticity and behavior, and that astrocytic MAGL converts 2-AG to neuroinflammatory prostaglandins (882).…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…The MAGL enzyme is present in postsynaptic astro-glial compartments [56][57][58] and it hydrolyzes 2-AG to form ARA and glycerol. There is some redundancy in degradation enzymes for 2-AG because ABHD6 (Abhydrolase domain containe protein 6) and ABHD12 can also hydrolyze 2-AG [48,56].…”
Section: -Ag Metabolismmentioning
confidence: 99%